Properties and manufacture technique of the functional bamboo charcoal/metal complex fabrics. (September 2014) - Lin, Ching-Hui; Chen, An-Pang; Lin, Jia-Horng
Functional textiles of far infrared emissivity and electromagnetic shielding are attracting increasing attention, thus in this research we fabricated the bamboo charcoal/metal complex yarns with stainless steel wires or copper wires as the core yarn and bamboo charcoal polyester textured yarn as the wrapped yarn, using a rotor twister machine. The two manufacture parameters were rotor speed (7000–11, 000 r/min) and wrapped number (2–7 turns/cm), and the bamboo charcoal/metal complex yarns which had optimum breaking strength and elongation became the weft yarns of the bamboo charcoal/metal complex woven fabrics. After the complex woven fabrics were tested in tensile strength and tensile strain, they were changed with different lamination numbers for the tests of the far infrared emissivity, anion density and air permeability. When the core yarn was 80 ìm stainless steel wires, the complex woven fabrics had the optimum tensile strength and air permeability of 364.8 N and 174.8 cm 3 /s/cm 2 . When the lamination number was 2, the complex woven fabrics had the optimum far infrared ray emissivity of 0.94.